Dynamics of knowledge creation in intra-organizational networks - Passos, Clotilde (2019)
Introduction: Knowledge has shown growing importance in economy, as a differentiation factor and a competitiveness enhancer, being considered as an important pillar of modern society development. Networks within and between organizations, as a strategy to potentiate knowledge sharing might be considered one of the most important approaches an organization may adopt. Objectives: To evaluate how the dynamics of knowledge creation occur in an intra-organizational network. Methods: This study is developed according to a descriptive and exploratory typology and uses the methodology of a case study developed over an optical services network in Portugal. Results: The results present evidence that the context of an intra-organizational network may favor a collective learning environment, mainly represented by the interaction that occurs between the collaborators of the various units and with the help of several “interaction” and knowledge creation spaces. Conclusions: The potential attributed to knowledge and networks in promoting the best organizational practices justify the interest of this analysis and the contribution of this study to the business environment.